Alur Evaluasi Materi Ajar Bahasa Inggris Kurikulum 2013 - Mayuasti Mayuasti; Hevriani Sevrika (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2015)
In 2013 the government has launched a new curriculum for applied and implemented at all levels of education, starting from elementary school (SD), Junior High School (SMP), High School (SMA), and Level College or University. However, there still exists some problem in the implementation the curriculum 2013, the national education minister decided to postpone its implementation for schools - a new  school  run  first  semester.  While,  for  schools  that  have  conducted  one  or  more  years  may  continue  to  use  it.  Due  to  these circumstances, the researchers decided to select a few schools that exist in the city of Padang and West Sumatra that were already implementing the curriculum in 2013.To determine the development of a new curriculum, there should be an evaluation, namely the evaluation of teaching materials used by teachers in implementing the curriculum, 2013. From the research that has been conducted, the researchers found that of all schoollevels, namely junior and senior high schools in and outside the city of Padang ( West Sumatra), there are three things that have been found. First, all the material presented teachers and learning process (PBM) already is in accordance with the curriculum of 2013. Second, the material provided in accordance with the teaching indicator. Third, based on the indicators according to experts; Nunan, and Maley, 90% indicator is found in the teaching materials used by teachers - teachers in junior and senior high schools in and outside thecity of Padang (West Sumatra). Finally, the researcher construct a model which represents the cycles of teaching material evaluation.